2011
DOI: 10.4012/dmj.2010-043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of laboratory light sources on the wear characteristics of indirect composites

Abstract: The purpose of the current study was to evaluate the influence of light sources on the mechanical properties and wear characteristics of indirect composite materials. The two composite materials used were Estenia C&B and Epricord. The three laboratory polymerization units used, of which the wavelength range was 400-500 nm, were Hyper LII (two metal halide lamps of 4.82 mW/cm 2 ), -Light II (one halogen lamp and two fluorescent tubes of 3.60 mW/cm 2 ), and Labolight LV-II (three fluorescent tubes of 0.63 mW/ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Resin composites consist of a polymeric matrix and reinforcing fillers, which could be ceramics, glass, glass ceramics, organic or composite 6) . The physical properties, color stability, and wear resistance of the resin composite are influenced by the extent to which it is polymerized [7][8][9][10][11] . In general, the wear resistance of the resin composite may be improved by enhancement of polymerization 8,9) .…”
Section: Introductionmentioning
confidence: 99%
“…Resin composites consist of a polymeric matrix and reinforcing fillers, which could be ceramics, glass, glass ceramics, organic or composite 6) . The physical properties, color stability, and wear resistance of the resin composite are influenced by the extent to which it is polymerized [7][8][9][10][11] . In general, the wear resistance of the resin composite may be improved by enhancement of polymerization 8,9) .…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid ceramics in Estenia are also advanced composite materials with high reinforcement resistance, which is the result of the loading of a resin matrix containing a micro-filler with a high proportion of nano-filler particles. Hirata et al 43) reported that the wear of Estenia was smaller than that of Epricord. In this study, the resin Epricord displayed significantly lower fracture strength than Estenia.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few studies that have used dental alloys and dental ceramics as rod specimens. It is possible to easily manufacture a precise rounded rod specimen composed of dental alloys or heat-pressed ceramics using the conventional lost-wax technique 5,18,19) . The purpose of this study was to evaluate the influence of ceramic surface texture on the wear of opposing gold alloy and heat-pressed ceramics.…”
Section: Introductionmentioning
confidence: 99%